Comprehensive Review of P2-Type Na2/3Ni1/3Mn2/3O2, a Potential Cathode for Practical Application of Na-Ion Batteries - Zhang, Jiaolong; Wang, Wenhui; Wang, Wei; Wang, Shuwei; Li, Baohua (ACS applied materials & interfaces, 2019)
P2-type Na2/3Ni1/3Mn2/3O2 is a promising cathode material for practical applications in Na-ion batteries, due to its high energy density, high volumetric capacity, excellent Na ion conductivity, ease of synthesis, and good stability in air. Yet, it is subject to structural rearrangements on charging to high voltage/low Na content and Na+/vacancy ordering transitions, which lead to poor reversibility and dramatic capacity decay upon cycling. In this Review, we present the latest advances related to Na2/3Ni1/3Mn2/3O2, with a main focus on strategies to stabilize the structural framework and improve the electrochemical properties. Practical issues and challenges are also proposed on the basis of current research status and progress.